Molecular mechanisms of D-cycloserine in a fear extinction posttraumatic stress disorder (PTSD) animal model - Malan-Muller, Stefanie (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.